EDUKASI PENCEGAHAN ANEMIA REMAJA PUTRI SMAN 14 BATAM - Julianawati, Tinta Julianawati; Tobing, Helly Dewi Yanita Br (Awal Bros Journal of Community Development, 2022)
Universities are expected to play an active role in providing education to the community for the realization of a prosperous society, including in terms of health. Adolescent girls are a group of people who need to get health education, especially those related to puberty, such as menstruation. Menstruation is an important thing for young women so that not many understand it well. Educational counseling on anemia prevention is needed to increase knowledge about anemia in adolescent girls which can be caused due to menstruation experienced every month. The educational activities carried out at SMAN 14 Batam are aimed at, among other things, 1.) Increasing knowledge about the condition of anemia in adolescent girls 2.) Providing awareness to be able to prevent anemia.